Fluorescence tuning of Zn(ii)-based metallo-supramolecular coordination polymers and their application for picric acid detection. Issue 11 (12th September 2016) - Li, Hong-Qing; Ding, Zhong-Yu; Pan, Yao; Liu, Chun-Hua; Zhu, Yuan-Yuan
Abstract : A series of metallo-supramolecular coordination polymers displayed strong and tunable visible luminescent emission and possessed the capability for detection of picric acid (PA) with high sensitivity and selectivity. Abstract : In this study, we report the synthesis of five one-dimensional Zn(ii )-based metallo-supramolecular polymersP0–4 through 1 : 1 complexation of Zn(SO3 CF3 )2 or Zn(ClO4 )2 with ditopic ligandsL 0–4 which contain two pyridine-dioxazole (pybox) units connected by a rigid conjugated oligo(1, 4-phenylene) linker. The new Zn(ii )-based polymers displayed relatively high quantum yields in solution and the solid state and showed tunable luminescent colors from blue to yellow owing to the conjugation effect of the ligand and the intra-ligand charge transfer (ILCT) between the coordination site and the chromophore of the ligand. Moreover, the polymer solution could exhibit white light emission by simply regulating the metal/ligand ratio or mixing different polymers. The polymers have been further explored as fluorescent chemosensors (FCs) for detecting nitroaromatic explosives. Among others, P1 possessed the highest capability for detecting picric acid (PA).